Early DNR in Older Adults Hospitalized with SARS-CoV-2 Infection During Initial Pandemic Surge. (December 2022) - Shah, Shalin; Makhnevich, Alex; Cohen, Jessica; Zhang, Meng; Marziliano, Allison; Qiu, Michael; Liu, Yan; Diefenbach, Michael A.; Carney, Maria; Burns, Edith; Sinvani, Liron
The role of early Do Not Resuscitate (DNR) in hospitalized older adults (OAs) with SARS-CoV-2 infection is unknown. The objective of the study was to identify characteristics and outcomes associated with early DNR in hospitalized OAs with SARS-CoV-2. We conducted a retrospective chart review of older adults (65+) hospitalized with COVID-19 in New York, USA, between March 1, 2020, and April 20, 2020. Patient characteristics and hospital outcomes were collected. Early DNR (within 24 hours of admission) was compared to non-early DNR (late DNR, after 24 hours of admission, or no DNR). Outcomes included hospital morbidity and mortality. Of 4961 patients, early DNR prevalence was 5.7% (n = 283). Compared to non-early DNR, the early DNR group was older (85.0 vs 76.8,   P  < .001), women (51.2% vs 43.6%,   P  = .012), with higher comorbidity index (3.88 vs 3.36,   P  < .001), facility-based (49.1% vs 19.1%,   P < . 001), with dementia (13.3% vs 4.6%,   P  < .001), and severely ill on presentation (57.9% vs 32.3%,   P  < .001). In multivariable analyses, the early DNR group had higher mortality risk (OR: 2.94, 95% CI: 2.10–4.11), less hospital delirium (OR: 0.55, 95% CI: 0.40–.77), lower use of invasive mechanical ventilation (IMV, OR: 0.37, 95% CI: .21–.67), and shorter length of stay (LOS, 4.8 vs 10.3 days,   P  < .001), compared to non-early DNR. Regarding early vs late DNR, while there was no difference in mortality (OR: 1.12, 95% CI: 0.85–1.62), the early DNR group experienced less delirium (OR: 0.55, 95% CI: .40–.75), IMV (OR: 0.53, 95% CI: 0.29–.96), and shorter LOS (4.82 vs 10.63 days, OR: 0.35, 95% CI: 0.30–.41). In conclusion, early DNR prevalence in hospitalized OAs with COVID-19 was low, and compared to non-early DNR is associated with higher mortality but lower morbidity.